Economics of Biofertilizer Application on Production of Planting Propagules of Teak in a Commercial Nursery - Verma, R. K.; , Jamaluddin; Dadwal, V. S.; Thakur, A. K. (Indian Forester, 2008)
Effect of application of biofertilizers, Azospirillum, phosphate-solubilising bacteria (PSB) and arbuscular mycorrhizal (AM) fungi was studied in a factorial experiment on production of planting propagules (stumps) of teak in nursery. Seed germination was maximum in Azospirillum treatment followed by its combination with AM and PSB after two months. Maximum height of seedlings was recorded in AM + Azospirillum, AM + PSB and AM+PSB+ Azospirillum combination after five months. Diameter of seedlings at collar region was maximum in AM, AM + Azospirillum and AM + Azospirillum + PSB combinations. The economics of biofertilizer application is also worked out. Application of biofertilizers increase the number of stumps produced per bed as well as the diameter of stumps. Therefore, an artificial profit index was calculated combining the both parameters to infer the real benefit of biofertilizers’ application. Based on the profit index application of AM fungi along with Azospirillum was found the best treatment to produce quality planting propagules of teak in a commercial nursery.